Correlates of the Dark Tetrad - Adrian Furnham; Stephen Cuppello (Acta Psychologica, 2024)
This study explored demographic, ideological, self-rating and personality traits correlates of the Dark Tetrad (DT4) which measures Narcissism (Special), Machiavellianism (Crafty), Psychopathy (Wild), and Sadism (Mean) traits. In total, 447 adults completed three tests: a bright-side, work-related, personality test (HPTI: High Performance Type Indicator), a dark-side test (Short Dark Tetrad) and a number of self-ratings. Correlations and regressions showed that all four dark traits were associated with low Adjustment (Neuroticism), but also with high Risk-Taking and Competitiveness (low Agreeableness). The various measures accounted for a third of the variance in explaining the Mean (Sadistic) score, and 40 % for Special (Narcissism). Trait Competitiveness was most closely associated with all four dark traits.